Seasonal dynamics of magnesium in rangeland areas of Southeastern region of Rio Grande do Sul State/Brazil: 1. field research - Ana Carolina Fluck; Michelle de Almeida Ollé; Hero Alfaya; José Carlos Leite Reis; João Gilberto Corrêa da Silva (Pesquisa Agropecuária Gaúcha, 2022)
We aimed to evaluate the seasonal dynamics of magnesium (Mg) in the system soil - plant - animal. It was conducted in two natural rangeland areas on two types of undisturbed soils (medium-clayey texture) in the Serra do Sudeste region (Rio Grande do Sul State, Brazil). In each area, 12 heifers were kept under continuous extensive grazing for twelve months without mineral supplementation. Samples of soil and vegetation were collected monthly from 16 fixed points and blood serum from each of the animals in each area monthly for the determination of Mg levels. The data were analyzed by analysis of variance, decomposition of the annual variation of the response variables and regression (harmonic analysis) for adjustment of function to express this variation. The Mg content in the soils of the two areas was high (1.86 ± 0.045 cmolc.dm-3). Mg levels in the vegetation (0.23 ± 0.0025 % DM) are sufficient to meet the needs of all categories of ruminants. The Mg contents in the blood serum (3.05 ± 0.0025) of grazing animals are considered medium to high and in normal levels. Mg supplementation is suggested in the cold season months for the most demanding animal categories (gestating and lactating females).